A surprising arrangement pattern and phylogenetic consideration: the complete mitochondrial genome of Belanger's croaker Johnius belangerii (Percoidei: Sciaenidae). (August 2015) - Xu, Tianjun; Tang, Da; Jin, Xiaoxiao
Abstract The complete mitochondrial genome of Johnius belangerii has been determined for the first time in this article. It was 19, 154 base pairs in length, and is composed of 37 genes (13 protein-coding genes, 22 tRNA genes and 2 ribosomal RNA genes). Totally, 5 notable non-coding regions were observed, and a non-coding of 1091 bp was identified as control region based on its location and AT richness. An 800 bp tandem repeat sequence was identified in the fifth non-coding region. We investigated the mitochondrial gene arrangement pattern and found that that the tRNAVal, 12SrRNA, 16SrRNA and tRNAPhe genes of J. belangerii mitogenome were orderly placed at the beginning of heavy strand. This order is different from other croakers. Combine with the phylogenetic reconstruction and genes arrangement pattern of J. belangerii mitochondrial genome, we consider J. belangerii is the most ancient genus within family Sciaenidae.